Agustinus Gianto y Peter Dubovský (eds.), Changing Faces of Kingship in Syria-Palestine 1500–500 BCE. Alter Orient und Altes Testament 459. Münster, Ugarit-Verlag, 2018. 206 pp. Hardback. ISBN 978-3-86835-283-2 - Pfoh, Emanuel (2019)
Fil: Pfoh, Emanuel. Universidad Nacional de La Plata; Argentina